Modeling the wear process of the ring/liner conjunction considering the evaluation of asperity height distribution. (August 2017) - Meng, Xianghui; Gu, Chunxing; Zhang, Di
Abstract: This paper presents a combined mixed lubrication and wear model to study the running-in process of the ring/liner system. In this model, the elastic-plastic asperity deformation is considered, as well as the evolution of asperity height distribution due to the asperity plastic deformation and wear. Meanwhile, the wear is computed with the Archard's wear law based on the asperity contact load. In this way, variations of friction loss, wear depth and surface morphology are obtained for the whole rubbing process. It is found that in the initial stage of running-in process, the effect of the asperity height distribution induced by asperity plastic deformation on the mixed lubrication performance is significant and even exceeds the contribution of wear. Highlights: A two-scale mixed lubrication and wear model is presented. The evolution of asperity height distribution is considered. The liner surface is decomposed into plateaus (local) and grooves (globe). It shows that asperity flatten effect on lubrication exceeds wear in initial stage.